Pengaruh Pengembangan Karier dan Komitmen Karyawanterhadap Kinerja Karyawan di Radar Malang - Novi Dian Kristin; Sri Wilujeng; Dianawati Suryaningtyas (Fakultas Ekonomika dan Bisnis Universitas PGRI Kanjuruhan Malang, 2019)
The study is determine the effect of career development and employee commitment on employee performance at Radar Malang. This research was conducted at Radar Malnag. The population in this study amounted to 40 employees using saturated sample techniques. This research uses descriptive and explanatory research, this type of research is quantitative research. In this study shows the influence partial and simultan. Partial effect of career development on employee performance, employee commitment to employee performance. While the simultan influence of the career development and employee commitment to employee performance.